Policy Network in Developing the Baros Tourism Village in Bandung Regency - Rizky Ilhami (SEAN Institute, 2023)
Baros Tourism Village has attracted attention as a tourism potential that has not been fully explored in the region. In the context of tourism development, public policy plays a crucial role. This research aims to analyze and understand the policy network involved in the development of the Baros Tourism Village in Bandung Regency. This research uses descriptive analytical methods with a qualitative approach to document and analyze interactions between various relevant stakeholders in the decision-making process. The research results show that good cooperation between the village government, community groups and tourism users plays an important role in the development of the Baros Tourism Village. Although formal structures are not clearly visible, the balance of power and shared goals have helped create an environment conducive to sustainable tourism development. The adoption of adaptive and innovative strategies also indicates awareness of the importance of adapting to changes in the environment and tourist needs, while still paying attention to preserving the environment and local culture.